Relationship of The Degree of Head Injury Based on Glasgow Coma Scale (GCS) with the Arrival of Acute Post Concussion Syndrome (PCS) Onset in Post-Head Injury Patients in General Hospital Dr.M.Djamil Padang - Azriyantha, Muhammad Reza; Syaiful Saanin; Hesty Lidya Ningsih (Biomedical Journal of Indonesia, 2021)
A B S T R A C TBackground: Traumatic brain injury is the main cause of death in the populationunder the age of 45 years, and the fourth leading cause of death in the entire ofpopulation. Based on the degree of traumatic brain injury, it is commonly categorizedbased on the Glasgow Coma Scale (GCS). Post-Concussion Syndrome (PCS) is theset of somatic, emotional / behavioral and cognitive symptoms that occur after atraumatic brain injury. The aim of this study was to find out the prevalence andcorrelation of the degree of traumatic brain injury based on the Glasgow Coma Scale(GCS) and the emersion of Post-Concussion Syndrome (PCS) acute onset in patientswith head injuries Method: This study was a cross-sectional analytic study ofpatients who experienced Post-Concussion Syndrome (PCS) after traumatic braininjury at DR. M. Djamil Hospital Padang in 2020 from June to November 2020. Datawere collected by filling in a questionnaire (The Rivermead Post ConcussionSymptoms Questionnaire) and medical record data of neurosurgical patients thatmet the inclusion and exclusion criteria. Result: : It indicated that 70 patients wereincluded in the inclusion criteria of this study. A total of 38 (54.3) respondents didnot undergo the acute onset of PCS, meanwhile respondents who experienced acuteonset of PCS were 32 (45.7) respondents. The results showed that 25 (67.6%)respondents with mild traumatic brain injury had PCS acute onset, while 4 (17.4%)respondents with moderate degree of traumatic brain injury had PCS acute onset,and 4 (17.4%) respondents had PCS acute onset PCS 3 (30%) respondentsexperienced severe traumatic brain injury with acute onset PCS and statistically thedifference in the proportion of data from each of these variables was significant witha p-value of 0.0001. The results of statistical tests showed that p value> 0.05 on thecorrelation between PCS and GCS, thus, it can be concluded that there was nocorrelation between the direction of the relationship between PCS and GCS.Conclusion There was no correlation between the degree of traumatic brain injurybased on GCS and the incidence of PCS acute onset, either it was unidirectional orvice versa in patients with head injuries at RSUP M. Djamil Padang.